GREEN ECONOMY EVALUATION OF EOR PROJECTS IN BORNEO FIELD: CASE OF CO2 INJECTION VS CHEMICAL INJECTION - Made Agusyasa, I
PT Borneo Petroleum Company (BPC) as one of the biggest oil and gas company in Indonesia is planning to perform Enhanced Oil Recovery in Borneo Field. It is considering performing chemical injection (CEOR) or CO2 injection. As CO2 injection requires bigger capital investment than CEOR, it becomes less favorable. However, as the campaign for Net Zero Emissions surges and the planning from the government to implement the carbon tax in Indonesia, the company must revisit the economic evaluation of the projects by introducing carbon tax in the calculation.